Second Language Acquisition in Cognitive Perspective: An Analysis of Mid-Pause of L2 Learners - Eka Parwati (Passage, 2017)
This study examines the relationship between narrative structure (tight and loose), English proficiency (Intermediate and Higher Intermediate) and the distributions of mid-pause of English students at Indonesia University of Education. This study employs a quantitative approach. Data were collected from narrating performance of 40 participants from English students at Indonesia University of Education. The performances were transcribed and the mid-pauses produced were analyzed by using paired t-test and independent t-test. The data analysis was based on cognitive information processing perspective (Schmidt, 1990). There are two important findings in this study. First, the findings show that L2 learners produce more mid-pauses when performing a tight structured narrative. Second, it is found that the performance of Higher Intermediate group is not affected by narrative structure. The findings may be useful for teacher and language tester as a consideration in choosing narrative task features to optimize the performance of learners.Keywords: mid-pause, tight structured narrative, loose structured narrative, cognitive perspective